2007
DOI: 10.1128/jb.01810-06
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Factor Tu3 (EF-Tu3) from the Kirromycin Producer Streptomyces ramocissimus Is Resistant to Three Classes of EF-Tu-Specific Inhibitors

Abstract: The antibiotic kirromycin inhibits prokaryotic protein synthesis by immobilizing elongation factor Tu (EF-Tu) on the elongating ribosome. Streptomyces ramocissimus, the producer of kirromycin, contains three tuf genes. While tuf1 and tuf2 encode kirromycin-sensitive EF-Tu species, the function of tuf3 is unknown. Here we demonstrate that EF-Tu3, in contrast to EF-Tu1 and EF-Tu2, is resistant to three classes of EF-Tu-targeted antibiotics: kirromycin, pulvomycin, and GE2270A. A mixture of EF-Tu1 and EF-Tu3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…A similar conclusion applies to the kirromycin producer Streptomyces ramocissimus. Remarkably, this organism has three tuf genes [245], one of which (tuf3) encodes a product (EF-Tu3) that is highly resistant to kirromycin, GE2270A and pulvomycin [167]. However, expression of tuf3 is marginal at the best of times and was not detectable during, or immediately before, kirromycin production.…”
Section: Target Ef-tu: Elfamycins Pulvomycin Ge2270amentioning
confidence: 96%
See 1 more Smart Citation
“…A similar conclusion applies to the kirromycin producer Streptomyces ramocissimus. Remarkably, this organism has three tuf genes [245], one of which (tuf3) encodes a product (EF-Tu3) that is highly resistant to kirromycin, GE2270A and pulvomycin [167]. However, expression of tuf3 is marginal at the best of times and was not detectable during, or immediately before, kirromycin production.…”
Section: Target Ef-tu: Elfamycins Pulvomycin Ge2270amentioning
confidence: 96%
“…By far the bulk of EF-Tu in this organism is encoded by tuf1 and is drug-sensitive. That, and the dominance of kirromycin-sensitivity over resistance, means that EF-Tu3 cannot possibly play any significant role in resistance, so S. ramocissimus must ensure its own well-being in some other, uncharacterized way [167].…”
Section: Target Ef-tu: Elfamycins Pulvomycin Ge2270amentioning
confidence: 99%
“…These strains still are able to produce kirromycin levels comparable to the wild type, indicating additional resistance mechanisms. A different kirromycin producer, S. ramocissimus, codes for 3 EF-Tu genes (tuf1, tuf2 and tuf3) [52], of which the gene product of tuf3 (EF-Tu3) displays a kirromycin-resistant phenotype [38]. The S. collinus Tü 365 genome codes for two elongation factors, EF-Tu1 (WP_020941664.1), and EF-Tu3 (WP_020938678.1) including a homolog to S. ramocissimus EF-Tu3.…”
Section: Kirromycinmentioning
confidence: 99%
“…This standard version is constitutively expressed and is sensitive to kirromycin. In 2007, it was shown that S. ramocissimus produces a minor quantity of EF-Tu from tuf3 in exponential phase, and this version of EF-Tu (65% amino acid homology to tuf1) is resistant to kirromycin (as well as pulvomycin and GE2270 A) (Olsthoorn- Tieleman et al, 2007). While this seemed like a plausible resistance mechanism for circumventing the toxicity associated with producing kirromycin, antibiotic synthesis actually occurs in stationary phase.…”
Section: Production Of Elfamycins In Bacteriamentioning
confidence: 99%
“…The strategy of inactivating one copy of tuf allowed a rush of studies identifying EF-Tu amino acid substitutions that conferred resistance to this understudied group of compounds. These studies, done in the late 1990s, are cited in modern reviews as tables of resistance mutations in EF-Tu; an example being Olsthoorn- Tieleman's (Olsthoorn-Tieleman et al, 2007) reporting of Abdulkarim's (Abdulkarim et al, 1994) findings of mutations causing resistance to kirromycin. However, this citation and others fail to mention the caveat that the original studies identifying these mutations were done in strains that contained one inactivated copy of EF-Tu (Abdulkarim et al, 1994;Mesters et al, 1994).…”
Section: Elfamycin Resistancementioning
confidence: 99%